Assessment of the Impact of the Relationship between the Human Development Index and the Unemployment Rate on Economic Growth - Nufa Visca Amaratya; Wulan Apriliani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
This research aims to evaluate the impact of the relationship between the Human Development Index (HDI) and the unemployment rate on economic growth. The study was conducted by analyzing economic and social data from various countries over a specific period. Regression analysis methods are used to understand the significance of the relationship between HDI, unemployment rate, and economic growth. The results show a strong correlation between HDI and economic growth, as well as a significant influence of the unemployment rate on economic growth. The policy implications of these findings are also discussed to provide guidance in efforts to enhance human development and sustainable economic growth.